Activities Reducing the Stress among Undergraduate Medical Students: The Students' Perception (Bangladesh Journal of Medical Education, 2019)
Most attention has been focused in recent years with respect to the issues of the medical students suffering from excess of stress during their studies, which may constrain their extent of learning, acquisition of knowledge, and consequently their academic performance. A cross-sectional descriptive study was conducted between July 2016 and June 2017 to explore the activities which helped to reduce the burden of stress among the undergraduate medical students of four government and two private medical colleges in Bangladesh. A self-administered semi-structured questionnaire was used to collect the data on the students' perception. A total of 1145 students included in this study of which 63 % were female. The study revealed that the students' perceptions of stress were highest with respect to the existing policy concerning vacation/holiday (87%), common room facilities (78%), counselling service (64%) and accommodation facilities (60%). The most common coping strategies adopted by the students were discussing problems with family members and friends, gossiping with friends and using social media. Neither alcohol nor drug consumption was mentioned by the students as an effective stress reduction strategy. To generalize the findings, a further longitudinal study including prospective and multi-center focus group discussions along with quantitative research is recommended.Bangladesh Journal of Medical Education Vol.10(1) 2019: 20-24